THE INFLUENCE OF SERVICE QUALITY AND PRICES ON CUSTOMER LOYALTY AT GOOL FUTSAL SURABAYA - Imroatus Faradila Sholichah; Awin Mulyati; Ute Chairuz M. Nasution (International Journal of Economic Integration and Regional Competitiveness, 2024)
Futsal is a combination of two words in Spanish: “futbol” which means football and “sala” which means room. The game is played by teams consisting of five players, including one goalkeeper. The aim of this research is to determine and analyze the combined influence of Service Quality and Price on Customer Loyalty at GOOL Futsal Surabaya. This study uses a quantitative approach. This research involved 100 futsal players who live in Surabaya. The results of this research are that service quality and price have a significant effect on customer loyalty at GOOL Futsal Surabaya. Service Quality and Price have a strong impact on Customer Loyalty. Thus, it can be concluded that Customer Loyalty is greatly impacted by the Quality of Service and Prices set by GOOL Futsal Surabaya.